Approximate Solution of Sub diffusion Bio heat Transfer Equation - Jagdish Sonawane; Bahusaheb Sontakke; Kalyanrao Takale (مجلة بغداد للعلوم)
In this paper, author’s study sub diffusion bio heat transfer model and developed explicit finite difference scheme for time fractional sub diffusion bio heat transfer equation by using caputo fabrizio fractional derivative. Also discussed conditional stability and convergence of developed scheme. Furthermore numerical solution of time fractional sub diffusion bio heat transfer equation is obtained and it is represented graphically by Python.